Pahangensin A and B, two new antibacterial diterpenes from the rhizomes of Alpinia pahangensis Ridley - Sivasothy, Y.; Ibrahim, H.; Paliany, A.S.; Alias, S.A.; Awang, Khalijah (Elsevier, 2013)
The rhizomes of Alpinia pahangensis Ridley yielded a new bis-labdanic diterpene for which the name pahangensin A (1) was proposed along with a new labdane diterpene, pahangensin B (2). Their structures were elucidated by spectroscopic methods including, 1D and 2D NMR techniques and LCMS-IT-TOF analysis. Pahangensin A (1) was found to be an antibacterial agent against Staphylococcus aureus, Bacillus cereus and Bacillus subtilis with MIC values less than 100 lg/mL, respectively. Pahangensin B (2) exhibited antibacterial activity (MIC <100 lg/mL) against B. cereus.